STRATEGI BANK XYZ DALAM MENINGKATKAN LOYALITAS NASABAH - Muhammad Saputra (Derivatif : Jurnal Manajemen, 2017)
XYZ Bank branch is trying to improve customer loyalty by focusing on service quality and customer satisfaction. To be able to answer the problem, the data were collected from 150 respondents from XYZ Bank branch by using a questionnaire. Furthermore, the data were analyzed using Structural Equation Modeling (SEM) analysis techniques. The results of analysis showed that (1) the service quality empirically affected satisfactions; (2) the service quality affected customer loyalty; and, (3) the customer satisfaction affected customer loyalty. Password: Service Quality, Satisfaction, Customer Loyalty